Zimbabwean Pentecostal Prophets: Rekindling the “True and False Prophecy” Debate - Vengeyi, Obvious (Prophets, Profits, and the Bible in Zimbabwe: Festschrift for Aynos Masotcha Moyo, 2013)
Since around 2009, Zimbabwe has witnessed an unprecedented surge of Christian preachers who call themselves prophets/esses. Characteristically, these so-called prophets/esses claim to work miracles; especially miracles that ‘contradict’ nature. This has earned them multitudes of both admirers and critics. Interestingly, while admirers and followers quote the Bible to endorse them as true prophets, critics and sceptics also cite the same Bible to characterise them as false prophets. The purpose of this article is to prove that by appealing to the Bible, both camps are wrong. The Bible does not have watertight criteria to distinguish true from false prophets. In other words, there is no distinction between a true and a false prophet in the Bible because fundamentally they are both called prophets! The article claims that the Bible is the source of confusion and not the solution to the debate regarding the distinction between true and false in the contemporary world.
free